2013
DOI: 10.4012/dmj.2013-082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between laser sintering and casting for retention of resin composite veneers to cobalt-chromium alloy

Abstract: The purpose of this study was to evaluate and compare the bond strengths between resin composite veneer and laser-sintered cobalt-chromium (Co-Cr) alloy with and without retention devices (Laser-R and Laser-N respectively). Cast Co-Cr alloy with and without retention devices (Cast-R and Cast-N respectively) were also prepared for fabrication technique comparison. Disk-shaped Co-Cr alloy specimens were air-abraded with alumina and veneered with a veneering system, Estenia C&B (ES) or Ceramage (CE). After 20,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Bond strength was higher for the photo/heat-polymerized (EST) gingiva-colored indirect resin composite than for the light-polymerized (CER) gingiva-colored indirect resin composite in all groups. These results are consistent with those of previous studies of bonding between indirect resin composites and metal alloys, which found photo/heatpolymerized indirect resin composites provided higher bond strengths than did light-polymerized indirect resin composites 25,26) , perhaps due to differences in the size of filler particles, the type of polymerization, and the mechanical properties of gingiva-colored indirect resin composites. Magne et al 27) reported that microtensile bond strengths between resin composites and resinluting material were affected by improved mechanical properties caused by heat treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Bond strength was higher for the photo/heat-polymerized (EST) gingiva-colored indirect resin composite than for the light-polymerized (CER) gingiva-colored indirect resin composite in all groups. These results are consistent with those of previous studies of bonding between indirect resin composites and metal alloys, which found photo/heatpolymerized indirect resin composites provided higher bond strengths than did light-polymerized indirect resin composites 25,26) , perhaps due to differences in the size of filler particles, the type of polymerization, and the mechanical properties of gingiva-colored indirect resin composites. Magne et al 27) reported that microtensile bond strengths between resin composites and resinluting material were affected by improved mechanical properties caused by heat treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Actually, many studies have shown that metalresin bonding is generally affected by surface treatments of the bonding area and adhesive systems (13)(14)(15)(16)(17). To enhance metal-resin bonding, retention beads are frequently used and are suggested in metal-resin restorations, but macromechanical retention devices have many disadvantages, such as causing an overcontoured resin veneered restoration or an unpleasing esthetic result caused by reverberating of the retention beads under the composite veneer (13,16,18). In this study, no macro-mechanical retention devices were used because the aim of this study was to assess and compare showed that metal substructures with retention devices fabricated by laser sintering (DMLS) had higher SBS values than those fabricated by casting, while there were no statistical differences between the two techniques when the metal specimens were prepared without retention devices (18).…”
Section: Discussionmentioning
confidence: 99%
“…Eight specimens for each test group were thermocycled 20,000 times alternately between water baths held at 4 and 60°C, with a 1 min dwell time in each bath. Prior to tensile testing, cylindrical stainless steel rods (30.0 9 8.0 mm diameter) were bonded to the veneered The stainless steel rods were used to provide a handle for the tensile testing based on the procedure described in a previous report [25]. Tensile retention strengths were determined using a universal testing machine (AGS-10kNG: Shimadzu Corp., Kyoto, Japan) at a crosshead speed of 1.0 mm/min.Tensile retention strength was defined as the force at failure divided by bonded surface area (2.5 9 2.5 9 3.14 mm 2 ).…”
Section: Tensile Testmentioning
confidence: 99%
“…The authors previously reported that laser-sintered Co-Cr alloy specimens with retention devices provided better retention and higher retention strength than cast Co-Cr alloy specimens with retention beads [25]. However, little information is available on adhesive bonding between laser-sintered CoCr alloy and various resin composite veneering systems.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation